2013
DOI: 10.3109/07853890.2013.770637
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin-1 is an evolutionary-conserved memory-related protein up-regulated in implicit and explicit learning paradigms

Abstract: Introduction. Studies of synaptic plasticity using the marine mollusk Aplysia californica as model system have been successfully used to identify proteins involved in learning and memory. The importance of molecular elements regulated by the learning- related neurotransmitter serotonin in Aplysia can then be explored in rodent models and finally tested for their relevance for human physiology and pathology.Materials and methods. Herein, 2-DE gel-based electrophoresis has been used to investigate protein level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Another study showed by mass spectrometry that reggies were also upregulated during memory related strengthening of synapses in Aplysia (Monje et al, 2013) and during barrel cortex plasticity (Butko et al, 2013). These studies are consistent with the present results and emphasize the role of reggie in brain function and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Another study showed by mass spectrometry that reggies were also upregulated during memory related strengthening of synapses in Aplysia (Monje et al, 2013) and during barrel cortex plasticity (Butko et al, 2013). These studies are consistent with the present results and emphasize the role of reggie in brain function and synaptic plasticity.…”
Section: Discussionsupporting
confidence: 81%
“…That reggies are involved in important steps of synapse formation and plasticity was suggested by reports showing by mass spectrometry analyses that flotillin-1/reggie-2 is upregulated during learning-related events in Aplysia and during spatial memory formation in the mouse hippocampus (Monje et al, 2013). Flotillin-1/reggie-2 is downregulated in the cortical barrel fields after sensory deprivation (Butko et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These are six key steps in the molecular biological delineation of STM and its conversion to LTM both implicit (procedural) and explicit (declarative) memory (Kandel, 2012). Notably, Monje et al (2013) reported that studies of synaptic plasticity using the marine mollusk Aplysia californica as model system have been successfully used to identify proteins involved in learning and memory. The importance of molecular elements regulated by the learning-related neurotransmitter serotonin in Aplysia can then be explored in rodent models and finally tested for their relevance for human physiology and pathology (Monje et al, 2013).…”
Section: Signaling and Memorymentioning
confidence: 98%
“…An important insight provided by PubMed showing that in 1960 two papers were published while in 2012 354 publications appeared, with a peak (370 papers) in 2008. Notably, Monje et al (2013) using a translational approach-from invertebrates to rodents-reported an evolutionaryconserved memory-related protein upregulated in implicit and explicit learning paradigms.…”
Section: Serotoninmentioning
confidence: 99%
See 1 more Smart Citation